LITERASI MATEMATIS DAN KEMANDIRIAN BELAJAR SISWA MTs ELL-FIRDAUS 2 KEDUNGREJA DALAM CASE BASED LEARNING - Vinda Putri Widyagesti; Fitrianto Eko Subekti (Jurnal Karya Pendidikan Matematika, 2023)
This study aims to: 1) determine the influence of Case-Based Learning on students' mathematical literacy skills and 2) determine the influence of Case-Based Learning on students' self-directed learning. This research is quasi-experimental, and the design employs a posttest-only control design. The population for this study consists of eighth-grade students at MTS Ell-Firdaus 2 Kedungreja. Sampling was conducted using the cluster random sampling technique. Data for this research were collected through instruments including mathematical literacy skills tests and self-directed learning questionnaires. The results of this study indicate that Case-Based Learning influences students' mathematical literacy skills and self-directed learning. This influence is shown by the Mann-Whitney test results for the mathematical literacy skills test data with a significance level of Sig. = 0.000 < 0.05, indicating that Case-Based Learning influences students' mathematical literacy skills. Additionally, the t-test for the self-directed learning questionnaire data yielded a significance level of Sig. = 0.006 < 0.05, revealing that Case-Based Learning affects students' self-directed learning.